(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
In the twentieth century Rabindranath Tagore concentrated into creating prose-poems. We have seen Tagore to give recognition to colloquial language in ‘Sabujpatra’ magazine in 1914. For example this magazine includes the novel ‘Ghore Baire’ Rabindranath Tagore has modified many of his writings from one form to another often. We can find a lot of his personal letters modified as poems later on. Top recipients of his letters include Indira Devi, Ranu Adhikari, Nirmal Kumar Mahalanbish, and Pratima Devi. Some of these letters have been transformed and included as poems in the ‘Punascha’ poetry book. This book was published in 1932 and this book opened a new horizon in the field of prose-poem. This research aims to observe how personal letters may turn into universal poems. The poetry book Punascha’ has six poems transformed from letters. They are ‘Natak’, Fank’, ‘Patra’, ‘Sundar’, ‘Bicched’, Basa’. We can find construction of the letter differs from the poem as letter happens to be personal whereas the poem is universal. So it is seen that the words the poet telling in the letter is not included in the poem. Every poem of ‘Punascha’ is prose-poem. Tagore had been experimenting with this one form of poem from a while and these prose-poems are the beautiful outcome of his experiment. Prose-poems consist of small sentences, and non-finite verbs is used widely. Eg, “Cheleta school paliye khela korche Hanser bacha buke chepe dhore Pukurer dhare Ghater upor akla bose Somosto bikel belata” After so many experiments he found his own way of poems. In these transformed prose-poems he has deconstructed the subject object verb sequence of Bengali grammar. “Majhkhaner fank diye roddur asche mather upor” In prose poems he often used poem words like - ‘Nishithoratrer taraguli chire niye Jodi har gantha jai theshe Biswaboner dokne …’ So my main research includes a detailed discussion about the above-mentioned aspects of prose-poems modified from letter by Rabindranath Tagore.